RELATIONSHIP BETWEEN KNOWLEDGE DISSEMINATION, LEARNING SELF-EFFICACY AND TASK PERFORMANCE OF BUSINESS EDUCATORS (NAU Journal of Technology and Vocational Education, 2024)
This study determined the relationship between knowledge dissemination, learning self-efficacyand task performance of business educators in tertiary institutions in South-south Nigeria. Acorrelational survey design was adopted. The study population was 137 business educators fromuniversities in South-South Nigeria, which also made up the sample size. The instrument usedfor data collected was a questionnaire which was face validated by three experts. Its reliabilitywas measured using Cronbach alpha method and an overall alpha value of 0.892 was obtained.Data collected were analyzed using, mean, standard deviation and regression with biascorrected bootstrap. The study found that knowledge dissemination does not predict learningself-efficacy of business educators. However, knowledge dissemination and learning self-efficacyseparately predict task performance of business educators in South-South universities inNigeria. Based on the findings it was recommended that, universities management shouldencourage knowledge dissemination as this will lead to high task performance of businesseducators in institutions, and business educators should make effort to improve on themselves byattending academic workshops and seminars as this will make them efficacious and optimallyenhance their task performance.
Keywords: Business education, knowledge dissemination, learning self-efficacy, task performance